The Formulation of Pentahelix Collaboration Model as for Developing the Tourism Attraction Potential of Tratasan Campsite, Magetan Regency - Purwanta; Nugraha, Favian Daniswara; Pratiwi, Maulydia Febrianti; Hidayati, Sinta; Nasieqoh, Cut Nabielatun; Saputra, Mardani Surya (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Tratasan Camping Ground possesses significant potential for development as a nature-based tourism destination in Magetan Regency. However, suboptimal management and limited engagement from the community and stakeholders pose major challenges to its growth.This study aims to identify the potential, challenges, and development strategies for Tratasan Camping Ground using the pentahelix collaboration, which involves the government, academia, businesses, communities, and media. The study utilised a multifaceted approach, incorporating interviews with various stakeholders to ascertain the prevailing conditions pertaining to Tratasan’s tourism sector, field observations, documentation, and literature reviews.The analysis revealed that Tratasan Camping Ground boasts numerous attractions, including its pristine natural beauty, its advantageous geographical location, and its considerable potential for the development of ecotourism. Nevertheless, the study identified several key challenges, namely a paucity of effective stakeholder collaboration, resulting in inadequate infrastructure development, minimal community involvement, and suboptimal tourism promotion. To address these challenges, a Pentahelix-based analytical framework is adopted to enhance stakeholder collaboration, the pentahelix collaboration model was adopted to enhance synergy between stakeholders, with the aim of improving infrastructure, empowering local communities, and optimising tourism promotion.The findings of this study conclude that the development of Tratasan tourism requires multi-stakeholder collaboration to maximize its potential and generate economic and social benefits for the local community.